2007
DOI: 10.1148/radiol.2441060425
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer: Body-Array versus Endorectal Coil MR Imaging at 3 T—Comparison of Image Quality, Localization, and Staging Performance

Abstract: Image quality and localization improved significantly with ERC imaging compared with BAC imaging. For experienced radiologists, the staging performance was significantly better with ERC imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
173
3
12

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(214 citation statements)
references
References 42 publications
12
173
3
12
Order By: Relevance
“…A few studies assessed the additional value of the use of an ERC for prostate MRI at 3.0 Tesla. These studies demonstrated an incremental benefit for image quality using an ERC [4,7,8] . However, it remains unclear if further improved SNR at 3.0 Tesla by an ERC improves diagnostic performance [9] .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A few studies assessed the additional value of the use of an ERC for prostate MRI at 3.0 Tesla. These studies demonstrated an incremental benefit for image quality using an ERC [4,7,8] . However, it remains unclear if further improved SNR at 3.0 Tesla by an ERC improves diagnostic performance [9] .…”
Section: Discussionmentioning
confidence: 87%
“…The findings correspond to the results of a study by Wagner et al [3] at 1.5 Tesla with ERC that found no significant effect of intravenous or intramuscular administration of HBB for visualisation of the prostate, neurovascular bundles, pelvic lymph nodes, and overall image quality. Studies promoting the use of HBB for pelvic MRI emphasize the advantage of suppressing bowel peristalsis to reduce motion artefacts [4,7,8] , which is particularly the case in MR-sequences with long acquisition times such as T2w TSE sequences [9] . Nevertheless, motion artefacts were comparably low in both of our assessed groups, which could be explained by the anatomical distance between the prostate and small bowel.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the endorectal coil on compression of the PZ glandular tissue and hence on T 2 has not formally been investigated, although, given the data in this study, the use of an endorectal coil is unlikely to cause significant reduction in PZ T 2 and compromise tumour to PZ contrast. In a study of 46 patients done with and without an endorectal coil at 3.0 T, the diagnostic performance of T 2 W imaging was improved in the former because of increased spatial resolution [27].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic performance has improved as new technological developments such as endorectal coil imaging and increasing field strengths has allowed for imaging at higher resolutions (2)(3)(4). The T2W-RARE applies a 2D sampling regime.…”
mentioning
confidence: 99%